2021
DOI: 10.1002/ldr.3917
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of land‐use changes and their future trends using spatial analysis and the CA‐Markov model—A case‐study with a special emphasis on aquaculture development in India

Abstract: Land resources utilized for aquaculture development have raised many environmental issues worldwide. But no detailed information is available about the land-use changes due to aquaculture in comparison with other land use modifications. Hence, the land-use changes and predictions have been explored in India's leading aquaculture region using multitemporal satellite images , spatial techniques, and land change modeling. Agriculture was the largest proportionate land use in the study area and consistently used f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Simulation of land‐use patterns based on the cellular automata (CA) model is well established. The commonly used CA simulation models in recent years include the FLUS and geographical simulation and optimization system (GeoSOS) models (Jayanthi et al, 2021). The future land use simulation (FLUS) model uses artificial neural networks to couple different driving factors to calculate the cell's land adaptability probability and adaptive inertia and competition mechanisms to solve the complexity and uncertainty of the conversion of different land‐use types.…”
Section: Methodsmentioning
confidence: 99%
“…Simulation of land‐use patterns based on the cellular automata (CA) model is well established. The commonly used CA simulation models in recent years include the FLUS and geographical simulation and optimization system (GeoSOS) models (Jayanthi et al, 2021). The future land use simulation (FLUS) model uses artificial neural networks to couple different driving factors to calculate the cell's land adaptability probability and adaptive inertia and competition mechanisms to solve the complexity and uncertainty of the conversion of different land‐use types.…”
Section: Methodsmentioning
confidence: 99%
“…LUESP, as an important way to maintain ecological land security and sustainable development, has attracted a lot of attention, and the regulation and simulation of LUESP through various models has become research ‘hot topics’ (Fan et al, 2018; Fu et al, 2021; Xie et al, 2019). Previous studies have indicated that the static simulation has shifted to dynamic simulation in the focus of land‐use pattern simulation, which prompts the maturity of the dynamic simulation model (Zhu et al, 2020), and others such as the cellular automata (CA) model (Jayanthi et al, 2021; Ma, 2020; Yang et al, 2012), multi‐agent system (MAS) (Tian et al, 2016), the CLUMondo model (Wang et al, 2020; Zhu et al, 2020), and the CLEU‐S model (Huang et al, 2019; Liu et al, 2017). However, current progress with land‐use ecological security regulation simulation research is still deficient in the following two aspects.…”
Section: Introductionmentioning
confidence: 99%
“…Assessing, simulating, and predicting changes in LULC is beneficial to land use planners and decision-makers, helping them to formulate plans in a sustainable and responsible way ( Jayanthi et al., 2021 ). Models are especially useful for addressing this problem.…”
Section: Introductionmentioning
confidence: 99%